Uji Aktivitas Hepatoproteksi dan Toksisitas Akut dari Ekstrak Gambir Terstandarisasi - Hasti, Syilfia; Muchtar, Husni; Bakhtia, Amri (Jurnal Penelitian Farmasi Indonesia, 2013)
Hepatoprotective activity and acute toxicity from extract of gambir (Uncaria gambir. Roxb) was investigated. The animals were groupedinto seven groups which consist of 5 female mice for each group. Mice from group I were only administrated orally with palm oil, 1% frombody weight for two days and 1% of gum suspension orally at day two. Group II were given CCl4 with dose 1.25 ml/kgbw in 10% of palm oilfor two days and gum suspension orally 1 hour after CCl4 given at day two. Group III, IV, V were given CCl4 with dose 1.25 ml/kgbw in 10%of palm oil for two days and followed by administration of gambir suspension orally 1 hour after CCl 4 given at day two with concentrations30; 100 and 300 mg/kgbw, respectively. At day 3, all the blood were taken and were examined its SGOT and SGPT. While the isolated liverwere weighed and the ratio between liver weight and body weight of mice were also observed. Acute toxicity test was conducted using fiveanimal groups consist of 5 female mice and 5 male mice. Each of mice then was given gambir suspension orally with doses of 1; 2; 4; 8 and15 g/kgbw, respectively. LD50 was defined as dose which can cause 50% death of total mice from each group. The result can be concluded thatgambir extract was found to be active as hepatoprotective agent with dose 30; 100 dan 300 mg/kgbw. Futhermore, extract of gambir couldreduced the ratio of liver weight and based on the LD 50 value obtained (24 hours, >15 g/kgbw), gambir was classify as non toxic.